Manajemen Badan Usaha Milik Desa Dalam Meningkatkan Pendapatan Asli Desa (Pada Desa Wataliku Kecamatan Kabangka Kabupaten Muna) - Dilla, Ulfa; Qomariyah, Erni; Manguntara, La (REZ PUBLICA, 2020)
The purpose of this research is to know the implementation of the management of the village owned enterprises in increasing the village's original income in the village Wataliku District Kabangka Muna District. The methods used in this study are qualitative descriptive. Research location of Wataliku Village Kabangka District, Muna Regency. The types and sources of data used in this study are primary data and secondary data. In the process of data collection techniques used methods are observation methods, interviews, and documentation. Data obtained further processed using qualitative descriptive method is then directed to answer the problem in this research. Then it can be concluded that the implementation of the management of the village owned enterprises in increasing the village's original income to the village Wataliku is good enough because in the implementation is done in four stages namely, planning, organizing, mobilization, supervision.